Cak-Cok Greetings to the Community of Jatisrono Village North Surabaya City - Liyana Dian Prastiwi (Eduvest - Journal of Universal Studies, 2022)
This is motivated by the phenomenon of the greeting form used by the people of Kampung Jatisrono who use the form of greeting cak-cok as a form of greeting that is used daily. This research itself aims to produce a description of what greeting words are used in the conversations of the people of Kampung Jatisrono and to produce a description of the impact caused by the community with the form of greeting used cak-cok. By using the ethnomethodology method which is carried out based on the fact that the participants in an interaction create a social order in the interaction situation, it is found that based on the form of greeting used by a person, in placing himself, it can be seen whether the person is trying to create social distance or actually building closeness/familiarity, sense of belonging. respect or even demeaning, insulting someone is implied by the form of greeting he uses.